Stereo‐ and Regioselective Synthesis of Tricyclic Spirolactones by Diastereoisomeric Differentiation of a Collective Key Precursor. Issue 8 (11th January 2016) - Valerio, Viviana; Mostinski, Yelena; Kotikalapudi, Ramesh; Tsvelikhovsky, Dmitry
Abstract: A general, parallel, and collective synthesis of 5/5/5‐ and 5/5/6‐ring fusion topologies of tricyclic spiranoid lactones through the controlled cyclizations of easily accessible, common key precursors is described. The rapid composition of key cycloalkyl methylene precursors yielded an assembly of bicyclic diastereoisomeric iodolactones, which were individually converted into a wide range of tricyclic, angularly fused spiranoid lactones in a regioselective and stereodirected fashion through the diastereoisomeric differentiation of a collective key precursor. The critical stereochemical assignment of the bicyclic starting materials, as well as the tricyclic targets, was confirmed by X‐ray crystal structure determination. Abstract : Tricyclic spiranoid lactones : Assemblies of diastereoisomeric iodolactones, which were designed from key cycloalkyl methylene precursors, are converted into a wide range of tricyclic, angularly fused spiranoid lactones with different topologies by simple diastereoisomeric differentiation in a regioselective and stereodirected fashion (see scheme; d.r.=diasteromeric ratio; FG=alkene, alkyne, carbonyl; R 1, R 2 =H, alkyl, aryl, OH, alkene; n =1 or 2).